Pengaruh Literasi Keuangan dan Financial Technology terhadap Keberlangsungan Usaha pada UMKM Kuliner di Banjarmasin Timur - Kartika Kartika; Ahmad Rifani (Universitas Lambung Mangkurat, 2025)
This study aims to determine and analyze (1) the effect of financial literacy on business continuity in Culinary MSMEs in East Banjarmasin District. And (2) the effect of financial technology on business continuity in Culinary MSMEs in East Banjarmasin District. This research uses quantitative methods. Data collection was carried out by distributing questionnaires to 30 respondents who were Culinary MSMEs in East Banjarmasin District. The sampling technique used in this study is a type of nonprobability sampling with purposive sampling technique. The data analysis technique used in this research is multiple linear regression using SPSS 26 software. The results of this study indicate that financial literacy has a positive and significant effect on business continuity and financial technology has no effect on business continuity.